Determinants of Foreign Direct Investment Inflows into Uganda: 1987 – 2018 - T. Odongo (Business, Management and Economics: Research Progress Vol. 6, 2024)
This study investigates determinants of Foreign Direct Investment (FDI) inflows into Uganda in the period between 1987 and 2018 using Granger Causality Test and Vector Error Correction Model (VECM). Although the results from the Granger Causality Test in this study indicate domestic investment as the major determinant of FDI inflows into Uganda, VECM estimates however present electricity consumption as the major determinant of FDI inflows into the country both in the short and the long run. Nevertheless, in the short run, electricity consumption and GDP growth were indicated as the major determinants of FDI inflows into Uganda in the period under the review. The results above perhaps suggest that most of the FDIs that visited Uganda during this period were interested in the manufacturing sector which uses a significant amount of electricity thus making electricity the major driver of FDI inflows into the country. The study recommends that drivers of FDI inflows into Uganda should be promoted as this may help to encourage more FDIs to visit the country. Secondly, in order to encourage more FDI inflows into the country, long-run electricity supply should be promoted in Uganda by fast-tracking and consolidating intervention in electricity generation and transmission.